Modifikasi Tooling Striper Plate Pada Block Mesin Cross Pieces Cut Untuk Memperpanjang Masa Pemakaian Die Plate - Nugroho, Adi; Santoso, Agus (Greeners: Journal of Green Engineering for Sustainability, 2025)
Part stamping is a result of a production process called sheet metal forming, which is needed to produce the press part sheet metal plate or sheet , pressing dies as molds and pressing machines to produce it. This study aims to extend the use of masa stiper plate die plate by modifying the engine block cross pieces cutusing analysis response surfaces methodology ( RSM ) in the data analysis to optimize the value of the, punch and air pressure ( pressure) , modifications done on the tooling plate striper at block cutting machines cross pieces cut, from the modifications made previously discarded die platecan be reused in the production process without, opservasi of data processing with application minitab 16 , there is no influence between the mass use of the die plate against three fariasi parameters used. The modification process performed at striper tooling plate is on the right side of the bottom with a width of 26 mm and a gradual depth of 0.5 mm - 1.5 mm, modified subsequently assembled and used on the observations taken on the production line next if the value obtained using the program minitab 16, from the data obtained is used to find the optimum value on an analysis of response surfaces.